2023
DOI: 10.3390/rs15163926
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Advancements in Remote Sensing for Assessing and Monitoring Land Use and Land Cover Changes Impacts on Surface Water Resources in Semi-Arid Tropical Environments

Abstract: This study aimed to provide a systematic overview of the progress made in utilizing remote sensing for assessing the impacts of land use and land cover (LULC) changes on water resources (quality and quantity). This review also addresses research gaps, challenges, and opportunities associated with the use of remotely sensed data in assessment and monitoring. The progress of remote sensing applications in the assessment and monitoring of LULC, along with their impacts on water quality and quantity, has advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…In adherence to the PRISMA guidelines, a total of 60 research articles were identified and chosen, a process outlined in the form of the flowchart depicted in Figure 1. In the process of selection, we applied exclusion criteria similar to those utilized in recent review studies [5,[34][35][36].…”
Section: Research Methods and Literature Search Systematic Literature...mentioning
confidence: 99%
See 1 more Smart Citation
“…In adherence to the PRISMA guidelines, a total of 60 research articles were identified and chosen, a process outlined in the form of the flowchart depicted in Figure 1. In the process of selection, we applied exclusion criteria similar to those utilized in recent review studies [5,[34][35][36].…”
Section: Research Methods and Literature Search Systematic Literature...mentioning
confidence: 99%
“…In adherence to the PRISMA guidelines, a total of 60 research articles were identified and chosen, a process outlined in the form of the flowchart depicted in Figure 1. In the process of selection, we applied exclusion criteria similar to those utilized in recent review studies [5,[34][35][36]. The notable increase in published research concerning the utilization of geospatial technology in agricultural water management in India signifies the achievement of a distinct level of expertise in this domain.…”
Section: Research Methods and Literature Search Systematic Literature...mentioning
confidence: 99%
“…Integration of GIS and RS will assist in overcoming these issues and bridging data availability and accessibility gaps, as it enables analyzing and getting the maximum out of available remotely sensed data, to support science-based decisions that are based on solid and inclusive data (Kumar et al, 2015) along with the ability to quickly and efficiently update databases of environment and resources through constant monitoring and observations, particularly for long-term monitoring. (Mashala et al, 2023). All in a limitless scale of spatial coverage.…”
Section: Potential Contribution Of Gis In the Sudan Contextmentioning
confidence: 99%
“…Remote sensing data can capture changes in SOC concentrations over time. Repeated data acquisition allows for monitoring changes in SOC due to factors such as land use, climate, and management practices [46,47].…”
Section: Remote Sensing and Soil Organic Carbonmentioning
confidence: 99%